Pengendalian Kualitas Produk Songkok untuk Meminimalkan Cacat Produksi Menggunakan Metode Seven Tools - Moh Ririn Rosyidi; Nailul Izzah; Anik Rufaidah (Industrial Engineering, Engineering of Faculty, Universitas Kadiri, 2023)
Songkok is an iconic product from Gresik City which is a cultural heritage rich in meaning. Therefore, maintaining songkok quality needs to be done more carefully in order to maintain the integrity of this product in an increasingly competitive industry. Two Pendopo MSMEs are one of the largest songkok producing MSMEs in Gresik. However, this business is facing problems with the number of defective products produced. The purpose of this study is to minimize songkok production defects in MSMEs Two Pendopo. This research uses the seven tools method. With a total production of 4,250 units carried out over 25 working days, it was found that the largest defect was in irregular threads (4.6%). Control charts are used to monitor production variability. Remedial action involves training workers, repair of yarn material, and better environmental conditions. Periodic monitoring and evaluation is implemented to control product quality effectively.